Peran Public Relations Dalam Mempertahankan Citra Perusahaan Go To Pasca Merger - Carolina Fernanda Diaz Aprianto; Fina Malika Azmi; Rara Salsabila; Tria Patrianti (Student Research Journal, 2024)
The company merger between Gojek and Tokopedia, which has been carried out since 2021, aims to unite two different company ecosystems into a single entity with a wider reach. Therefore, the existence of Public Relations is needed in maintaining the image of the two companies that have become one. This study aims to determine the role of Public Relations in maintaining GoTo's corporate image after the merger. The theory used in this research is the theory of Dozier and Broom regarding the role of Public Relations in maintaining the company's image, including (1) expert preciber communication, (2) problem solving process facilitator, (3) communication facilitator and (4) technician. The method used in this research is descriptive qualitative method with data collection techniques through literature search, company documents, media monitoring, and observation. The results showed that with the role of Public Relations as a problem solving process facilitator and communication facilitator, the GoTo Company can handle issues regarding the policy of reducing incentives and employee layoffs quite well, so that GoTo's image can still be maintained